Neuroinduction and neuroprotection co-enhanced spinal cord injury repair based on IL-4@ZIF-8-loaded hyaluronan–collagen hydrogels with nano-aligned and viscoelastic cues. Issue 33 (3rd August 2022) - Xin, Nini; Liu, Xiaoyin; Chen, Suping; Zhang, Yusheng; Wei, Dan; Sun, Jing; Zhou, Liangxue; Wu, Chengheng; Fan, Hongsong
Abstract : We developed a nano-aligned and viscoelastic hydrogel matrix embedded with IL-4@ZIF-8. This biomimetic hydrogel combining neuroinductive cues and neuroprotective cues showed promising prospects in SCI repair. Abstract : Spontaneous recovery after spinal cord injury (SCI) is extremely limited since the severe inflammatory responses lead to secondary damage, and the diseased extracellular matrix (ECM) fails to provide inductive cues for nerve regeneration. To address these dilemmas, herein, we propose a biomaterial-based strategy combining neuroprotection and neuroinduction for SCI repair. Taking advantage of a microfluidic chip, we constructed imine-crosslinked aldehyde-methacrylate-hyaluronan/collagen hybrid hydrogel microfibers incorporating interleukin 4 (IL-4)-loaded ZIF-8 nanoparticles (IL4@ZIF-8 NPs). The hybrid hydrogel microfibers possess pivotal traits mimicking the natural ECM and hold neuroinductive nanoalignment and viscoelasticity, as well as the acidic microenvironment-responsive release of neuroprotective IL-4. Then, we elucidated the role of the tailored hydrogel microfibers in promoting the structural and functional recovery of SCI rats. The implanted hydrogel microfibers incorporating IL4@ZIF-8 NPs protected endogenous neural cells by promoting M2 polarization of recruited macrophages and suppressing inflammation. Additionally, the hydrogel microfibers enhanced neuronal differentiation, accelerated axonal regrowth, synapse formation and remyelination, resulting from their ECM-mimicking oriented nano-topography and viscoelasticity. Moreover, the locomotor function was also improved by the implanted microfibers combining neuroprotective cues and neuroinductive cues. This work not only paves the steps for the development of a novel class of multifunctional hydrogels that manipulate tissue behavior by modifying the cellular microenvironment but also provides intriguing insights for the repair of SCI and even other central nervous system (CNS) injuries via tissue engineering approaches.